Prevalence and risk factors of Bubaline subclinical mastitis in selected peninsular Malaysian states - Mohd Amin, Nor'Amira; Mohd Nor, Norhariani; Abu Bakar, Md Zuki; Sadiq, Mohammed Babatunde (Universiti Putra Malaysia, 2025)
Subclinical mastitis (SCM) is a common disease in dairy buffaloes worldwide, resulting in economic losses due to reduced milk production and quality. There is a dearth of information on the susceptibility to bubaline mastitis and the associated factors at farm and animal levels. This study determines bubaline mastitis's prevalence and risk factors in buffalo farms in Malaysia. A cross-sectional study was conducted at 12 buffalo farms across selected states in Peninsular Malaysia, including Selangor, Kedah and Penang. California Mastitis Test (CMT) was used to identify infected and non-infected buffaloes, whereas on-farm assessment and cross-sectional survey were conducted to collect farm and animal-based data. Data analysis was conducted using descriptive statistics, Chi-square test, and binary logistic regression. Overall, the prevalences of SCM at the quarter and animal levels were 29.7% (95% CI: 6.3%–49.0%) and 40.1% (95% CI: 0.0%–66.7%), respectively. While the animal-level prevalence of SCM was not significantly different across states, a significant difference was observed in the quarter-level prevalence (Selangor; 28.2% [95% CI 9.9–40.1], Kedah; 22.1% [95% CI: 6.3–33.3], Penang; 46.3% [95% CI: 43.2–49.0]). The prevalence of SCM bubaline was significantly associated with mastitis history (p < 0.001) at the animal level, pre- and post-teat dipping (p =0.041) and the absence of other dairy animals (p = 0.048) at the farm level. The findings reflect a high prevalence of SCM in buffaloes and the factors that can be considered in developing effective SCM prevention and control measures.